The good, the bad, and the aunties [large type] - Sutanto, Jesse Q. (Sutanto, Jesse Q. Aunties, 2024)
"After an ultra-romantic honeymoon across Europe, Meddy Chan and her husband Nathan have landed in Jakarta to spend Chinese New Year with her entire extended family. Chinese New Year, already the biggest celebration of the Lunar calendar, gets even more festive when a former beau of Second Aunt's shows up at the Chan residence bearing extravagant gifts--he's determined to rekindle his romance with Second Aunt and the gifts are his way of announcing his courtship. His grand gesture goes awry however, when it's discovered that not all the gifts were meant for Second Aunt and the Chans--one particular gift was intended for a business rival to cement their alliance and included by accident. Of course the Aunties agree that it's only right to return the gift--after all, anyone would forgive an honest mistake, right? But what should have been a simple retrieval turns disastrous and suddenly Meddy and the Aunties are helpless pawns in a decades-long war between Jakarta's most powerful business factions. The fighting turns personal, however, when Nathan and the Aunties are endangered and it's up to Meddy to come up with a plan to save them all. Determined to rescue her loved ones, Meddy embarks on an impossible mission--but with the Aunties by her side, nothing is truly impossible."--